A formula of evaluating structural safety based on fuzzy set theory - Huynh, Le Xuan; Duy, Le Cong (Vietnam Journal of Mechanics, 2011)
This article presents an approach to assess safety levels of structures. A new formula for determining the fuzzy reliability of structures is proposed for the case where the set of loading effect and set of structural durability are general fuzzy sets. Illustration example concerning the bending strength evaluation of a simple-beam structure, is presented with the choice of triangular fuzzy sets for loading effect and structural durability.